Estimating Economic Effectiveness of Economic Infrastructure: A Methodological Exploration - Rim, Gwang-Nam; Chang, Sun-Nam; An, Chol-Ju; Han, Ho-Yun (Finance & Economics Review, 2019)
Purpose: Economic Infrastructure is a prerequisite for economic development. To this end, it is necessary to reveal the theoretical background for estimating the effectiveness of economic infrastructure and establish the methodology for estimating the effectiveness. Until now, there have been a number of qualitative and quantitative studies that investigate the effect of infrastructure on the economy. However, we can hardly say that there is an agreed-upon methodology for estimating such effectiveness. The aim of this paper is to solve methodological problems arising in estimating the effectiveness of infrastructure in terms of economic, physical-value, and spatio-temporal aspects. Methods: The first section of the paper discusses theoretical problems for estimating the effectiveness of economic infrastructure. For this, we analyze the preceding studies on economic infrastructure as an economic concept, and on this basis, systemize its specific features and roles in a new way. The second section illustrates the main indicators and methodology for estimating the effectiveness of economic infrastructure. In this section, we apply various indicators related to physical and value aspects to suggest the methodology for estimating the space-time effectiveness of economic infrastructure. Results: Based on the drawbacks of the previous approaches, this paper finds the rationality to estimate the economic effectiveness of economic infrastructure using the benefit to cost approach rather than the functional approach. Implications: This study can be of significance to the policymakers or investors in decision-making related to infrastructural investment. They can calculate the economic effectiveness using the proposed methodology, upon which they can select optimal infrastructural projects for the short term or long term.